(untitled) (Journal of Asian Development Studies, 2025)
This paper highlights the unequal application of Rule 215 of the Punjab Prison Manual, which governs education-based remission for convicted prisoners. While the rule has been expanded to include religious minorities, its implementation remains structurally biased and institutionally exclusionary. The paper examines this discrimination through the lens of constitutional provisions, minority rights, and international human rights obligations. It explores the root causes of this disparity, including administrative negligence, lack of religious infrastructure, and policy gaps. Ultimately, it proposes legal and institutional reforms to ensure that the principle of equal protection is upheld within the prison system.